Guide Professionalism, Guide Services, Ship Security, and Shipping Safety for Smooth Ship Traffic at Indonesia's Main Ports - Syahrial Nasution; Muhammad Thamrin; Sri Rahardjo; Datep Purwa Saputra (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to analyze the quality of professionalism, guide services related to shipping safety, ship security which influences the smoothness of ship traffic in Indonesia's main ports. Sea ports that serve ships for loading and unloading activities, both for inter-island and international transportation, are generally required to guide. This research method uses descriptive quantitative with data collection techniques using questionnaires distributed to scouts and stakeholders at the port. The R-Square value for smooth ship traffic is 0.762, indicating that the variables of professional pilotage, pilotage services, shipping safety and ship security are able to explain around 76.2% of the variation in smooth ship traffic. This means that the professional factors of pilots, pilotage services, shipping safety and ship security have a major contribution to the smoothness of ship traffic. The R-Square value for shipping safety is 0.626, indicating that the professional guide and guiding service variables are able to explain around 62.6% of the variation in shipping safety. This shows a moderate contribution to the smoothness of ship traffic. The R-Square value of guiding services is 0.425 indicating that guiding professionals explain around 42.5% of the variation in guiding services. This indicates that although there is a fairly strong relationship, there are other factors that also influence guiding services.  The R-Square value of ship safety is 0.580, the pilot professional and pilot service variables explain around 58% of the variation in ship safety. This shows quite a significant influence, indicating that professional pilotage and pilotage services are an important factor in ship safety.